Expression of the mouse odorant receptor genes Olfr1507, Olfr1508, and Olfr1509 in gene-targeted strains - Segoviano Arias, Paola Luz Eréndida; Justus Liebig University Giessen (My University, 2024)
In mice, odorants are detected in the olfactory epithelium by olfactory sensory neurons (OSNs) via 1141 odorant receptors (ORs), which are G-protein-coupled seven-transmembrane proteins. The position of an OSN in the olfactory epithelium restricts gene choice to a subset of the repertoire of OR genes. A mature OSN expresses RNA of only one OR gene. Counts of OSNs expressing a given OR gene in mouse can vary greatly from gene to gene. One of the most frequently chosen OR genes is Olfr1507, previously referred to as MOR28. This gene is located on Chromosome 14 in a cluster that includes the highly homologous OR genes Olfr1508 and Olfr1509. In my Ph.D. thesis, I studied novel inbred C57BL/6 gene-targeted mouse strains carrying mutations of the OR-IRES-marker type in Olfr1507, Olfr1508, or Olfr1509. This genetic approach enables the visualization of OSNs (including the cilia, dendrite, cell body, axon, and axon termini) that express a given OR, by targeted integration of a cassette that leads to cotranslation of the OR with a marker such as taulacZ or tauGFP via an internal ribosome entry site (IRES). I examined the spatial pattern of OSNs that express Olfr1507, Olfr1508, or Olfr1509 in the olfactory epithelium of Olfr1507-IRES-tauGFP, Olfr1508-IRES-tauGFP, and Olfr109-IRES-tauGFP strains. By using immunohistochemistry, I located these OSNs to the dorsolateral and ventromedial regions of the olfactory epithelium. I found that Olfr1507 is expressed in four-fold more OSNs than Olfr1508 and in three-fold more OSNs than Olfr1509. I applied immunohistochemistry to characterize the positions of the Olfr1507, Olfr1508, or Olfr1509 glomeruli in the olfactory bulb and to test the specificity of a commercially available Olfr1507 antibody in the olfactory bulb. ∆OR strains have been used to study OR gene choice. In this paradigm, the coding region of an OR gene is replaced with that of a reporter such as GFP. The absence of Olfr1507-immunoreactive signal in homozygous ∆Olfr1507 mice is powerful evidence that the commercially available Olfr1507 antibody is specific for Olfr1507. I found that axons of ∆Olfr1507-expressing OSNs project diffusely over the ventral aspect of the olfactory bulb and innervate >100 glomeruli, suggesting there may be >50 OR gene candidates for second choice in these OSNs. Taken together, my studies have validated the specificity of the Olfr1507 antibody. Working with inbred gene-targeted strains led to a consistent number and positions of the Olfr1507, Olfr1508, or Olfr1509 glomeruli. OSNs expressing ∆Olfr1507 reside in the same area of the main olfactory epithelium as Olfr1507-expressing OSNs and project their axons to >100 glomeruli, with various apparent degrees of innervation.
Keywords: ddc:570